Understanding propaganda from the perspectives of general semantics / Mohd Rajib Ghani - Ghani, Mohd Rajib (CMIWS and UiTM Press, 2010)
Propaganda is making inroad in societies and its impact is so tremendous. Through the proliferation of the mass media and ICT, propaganda messages can reach the audience within a few seconds. Sometimes, manipulation, misinformation and disinformation do occur through propagandistic messages without readers realizing it. Nonetheless, not all propaganda is bad. Many scholars claim that “truth” is part of propaganda, for example, propaganda for peace is used during conflicts and insurgency. But bad propaganda, such as the maniacal Fuhrer Hitler’s evil intention to conquer all European nations is quite disastrous to mankind. This paper, introduces a general semantics approach of balance thinking as to evaluate language of propaganda. General semanticists always believe that the principle of general semantics is the last bastion of preconceived mind and bias inherent in propaganda messages. As Korzybski wrote, “it is probably no secret that a large part of the population of this world was swayed by propaganda during war”. And the interdisciplinary method of general semantics which is providing us a mechanism of evaluative habits of our everyday language and awareness may be useful for verbal peace movement.